Metabolic syndrome and the risk of adverse cardiovascular events after an acute coronary syndrome. (29th August 2020) - Cavallari, Ilaria; Cannon, Christopher P; Braunwald, Eugene; Goodrich, Erica L; Im, KyungAh; Lukas, Mary Ann; O'Donoghue, Michelle L
Abstract: Background: The incremental prognostic value of assessing the metabolic syndrome has been disputed. Little is known regarding its prognostic value in patients after an acute coronary syndrome. Design and methods: The presence of metabolic syndrome (2005 International Diabetes Federation) was assessed at baseline in SOLID-TIMI 52, a trial of patients within 30 days of acute coronary syndrome (median follow-up 2.5 years). The primary endpoint was major coronary events (coronary heart disease death, myocardial infarction or urgent coronary revascularization). Results: At baseline, 61.6% ( n  = 7537) of patients met the definition of metabolic syndrome, 34.7% (n = 4247) had diabetes and 29.3% had both ( n  = 3584). The presence of metabolic syndrome was associated with increased risk of major coronary events (adjusted hazard ratio (adjHR) 1.29, p  < 0.0001) and recurrent myocardial infarction (adjHR 1.30, p  < 0.0001). Of the individual components of the definition, only diabetes (adjHR 1.48, p  < 0.0001) or impaired fasting glucose (adjHR 1.21, p  = 0.002) and hypertension (adjHR 1.46, p  < 0.0001) were associated with the risk of major coronary events. In patients without diabetes, metabolic syndrome was numerically but not significantly associated with the risk of major coronary events (adjHR 1.13, p  = 0.06). Conversely, diabetes was a strong independent predictor of major coronary events in the absence of metabolic syndrome (adjHR 1.57, p  < 0.0001). The presence of both diabetes and metabolic syndrome identified patients at highest risk of adverse outcomes but the incremental value of metabolic syndrome was not significant relative to diabetes alone (adjHR 1.07, p  = 0.54). Conclusions: After acute coronary syndrome, diabetes is a strong and independent predictor of adverse outcomes. Assessment of the metabolic syndrome provides only marginal incremental value once the presence or absence of diabetes is established.